Pengaruh Sumber Informasi, Peran Bidan dan Peran Keluarga dengan Coping Stres Ibu Menghadapi Persalinan - Ni Putu Sri Laksmi Purwaningsih; Siti Hodijah (MPI Press, 2023)
Introduction: Increasing stress control in mothers giving birth needs to be done to increase the success of safe and comfortable deliveries in an effort to improve safety for babies and mothers during the delivery process. Objectives: The aim of the study was to determine the relationship between sources of information, the role of the midwife and the role of the family in coping with the stress of mothers facing childbirth at Budhi Asih Hospital, East Jakarta. Method: The research method used was quantitative analytic with a cross-sectional approach using primary data, the number of samples was 50 birth mothers who visited Budhi Asih Hospital, East Jakarta. Primary data collection was carried out by distributing questionnaires to respondents who fit the inclusion criteria. Data analysis used the Chi-Square test. Results: The results showed that mothers giving birth at Budhi Asih Hospital in 2022 were influenced by sources of information with a p-value of 0.010, the role of midwives with a p-value of 0.006 and the role of the family with a p-value of 0.013. Conclusion: The conclusion of the study is that there is a significant relationship between sources of information, the role of the midwife and the role of the family in coping with the stress of mothers facing childbirth at Budhi Asih Hospital.